Energy directed folding of RNA sequences. - Hogeweg, P (1984)
A modification of Nussinov's algorithm (1) for (planar) secondary structure generation is described. Our algorithm postpones decisions on matches involving destabiling loops until they prove to be energetically more favourable than more local matches. We present, moreover, an alternative way of representing secondary structures which avoids unwarranted suggestions on higher order neighbourhood, can be automated easily, allows for any amount of annotation of the sequences, makes comparison of alternate foldings easy and is pleasing to the eye. 5S RNA sequences are used to illustrate the methods.